Amberlyst-Promoted Eco-Friendly Route to 4-Arylpyrrolo[1,2-a]quinoxalines - Kishore Kumar Reddy, Ramireddy; Raju, Mogalagani; Penke, Vijaya Babu; Kotanka, Ramakrishna Reddy; Gandolla, Chinna Reddy (Synlett)
Herein, we have developed an Amberlyst-15-catalyzed oxidative cyclization strategy for the synthesis of biologically active pyrrolo[1,2-a]quinoxaline scaffolds. The advantages of the present protocol include catalyst recovery and reuse, along with simpler reaction conditions compared to previously reported methods.